Arqueologia do saber em Foucault: entre o a priori de Kant e a hierarquia de valores de Nietzsche: Archeology of the knowledge in Foucault: between the a priori of Kant and the hierarchy of values in Nietzsche - Dutra de Azeredo, Vânia (Modernos & Contemporâneos - International Journal of Philosophy [issn 2595-1211], 2022)
In this article, we propose a reading of Foucaultian archeology especially in The Order of Things through an approximation between the concept of a priori in the Foucaultian historicism and the transcendental concepts in Kant and the hierarchy of values in Nietzsche. In the first case, we aim to show that Foucault seeks to realize, in terms of the archeological procedure, a copernican revolution similar to Kants, notably, that in which concerns the radical change of history’s comprehension and the aiming at knowledge. In the second we propose that the concepts of order, rules, conditions of possibility frame a certain hierarchy of values, referring, with that, the discursive regularities and the systems of dispersal in each epistémê proposed by Foucault to a hierarchy of values, even though Foucault does not directly make such reference. Keywords: archeology, a priori historicism, value hierarchy; knowledge; epistémê